If α , β , γ are the roots of the equation x 3 − x − 1 = 0 , then determine the equation whose roots are 1 − α 1 + α , 1 − β 1 + β , 1 − γ 1 + γ .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
From Vieta's formula, we know that
α + β + γ = 0 α β + α γ + β γ = − 1 α β γ = 1
Now, we want to form an equation with roots 1 − α 1 + α , 1 − β 1 + β , 1 − γ 1 + γ
To simplify things, we let α = a + 1 , β = b + 1 , γ = c + 1
Our roots now are:
1 − ( a + 1 ) 1 + ( a + 1 ) , 1 − ( b + 1 ) 1 + ( b + 1 ) , 1 − ( c + 1 ) 1 + ( c + 1 ) = − a a + 2 , − b b + 2 , − c c + 2
The equations above become (do this yourself!):
( a + 1 ) + ( b + 1 ) + ( c + 1 ) = 0 ⟹ a + b + c = − 3 ( a + 1 ) ( b + 1 ) + ( a + 1 ) ( c + 1 ) + ( b + 1 ) ( c + 1 ) = − 1 ⟹ a b + a c + b c = 2 ( a + 1 ) ( b + 1 ) ( c + 1 ) = 1 ⟹ a b c = 1
Now, we find the coefficients for the new equation:
( − a a + 2 ) + ( − b b + 2 ) + ( − c c + 2 ) = − ( a b c b c ( a + 2 ) + a c ( b + 2 ) + a b ( c + 2 ) ) = − ( a b c 3 a b c + 2 ( a b + a c + b c ) ) = − ( 1 3 ( 1 ) + 2 ( 2 ) ) = − 7
( − a a + 2 ) ( − b b + 2 ) + ( − a a + 2 ) ( − c c + 2 ) + ( − b b + 2 ) ( − c c + 2 ) = a b ( a + 2 ) ( b + 2 ) + a c ( a + 2 ) ( c + 2 ) + b c ( b + 2 ) ( c + 2 ) = a b c c ( a b + 2 a + 2 b + 4 ) + b ( a c + 2 a + 2 c + 4 ) + a ( b c + 2 b + 2 c + 4 ) = a b c 3 a b c + 4 ( a b + a c + b c ) + 4 ( a + b + c ) = 1 3 ( 1 ) + 4 ( 2 ) + 4 ( − 3 ) = − 1
( − a a + 2 ) ( − b b + 2 ) ( − c c + 2 ) = − a b c ( a + 2 ) ( b + 2 ) ( c + 2 ) = − a b c a b c + 2 a b + 2 a c + 2 b c + 4 a + 4 b + 4 c + 8 = − 1 1 + 2 ( 2 ) + 4 ( − 3 ) + 8 = − 1
Use these values to form the equation:
x 3 − ( − 7 ) x 2 + ( − 1 ) x − ( − 1 ) = 0 x 3 + 7 x 2 − x + 1 = 0
Problem Loading...
Note Loading...
Set Loading...
Let y = 1 − x 1 + x .
Noting that x = 1 is not a solution to the equation x 3 − x − 1 = 0 , it can be 'safely' said that
y ( 1 − x ) = 1 + x ⟹ x = y + 1 y − 1
Substituting this value of x in the original equation, we get
( y + 1 y − 1 ) 3 − y + 1 y − 1 − 1 = 0 ⟹ ( y − 1 ) 3 − ( y − 1 ) ( y + 1 ) 2 − ( y + 1 ) 3 = 0
This simplifies to − ( y 3 + 7 y 2 − y + 1 ) = 0